The Nissen fundoplication in sliding hiatal hernia: indications, technique and results - Praderi, Luis Alberto (Cirugía del Uruguay, 2020)
A study is carried out of the indications, technique and results in 16 cases of hiatus hernia due to sliding and one esophagitis form cardiac fundus malformations treated with Nissen's funduplicature.